Ergonomic Analysis Regarding Work-Related Musculoskeletal Disorder Among Car Mechanics - Shamsudin, Shahril Izwan; Latifah Md Ariffin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Ergonomics, a critical component of occupational safety and health, aims to improve worker well-being and efficiency by enhancing safety, comfort, and productivity, thereby reducing injury risks. Despite its importance, ergonomics is still nascent in Malaysian workplaces. This study evaluates ergonomic standards in automotive workshop in Parit Raja, focusing on work-related musculoskeletal disorders (WMSDs). Using Self-Assessment Musculskeletal Pain Survey Form and ergonomic assessments with RULA and REBA method, the study identifies the prevalence of WMSDs and suggests preventive actions to improve workplace conditions and reduce physical strain.